PERILAKU SOSIAL INDIVIDU PEMAIN GAME ONLINE "PERFECT WORLD" DI DESA SEA SATU - Kapoh, Gerry F. (HOLISTIK, Journal Of Social and Culture, 2015)
The growth of the worldwide computer network known as the Internet is massively has facilitated the emergence groups of people who receive and share information, among others through conversation / chat via online media such as discussion forums, facebook, twitter, etc. One of today's online media are most influential in forming a large number of these people groups that interact and integrate is media online games (online games). Here will be studied, the social behavior of individual players online game "Perfect World", Also the change of their behavior within the family and society. Behaviors of individuals in a community is a form of interaction between individual characteristics with the characteristics of the community. Every individual in the community, everything will behave differently from each other and the behavior would be affected by each environment. Keywords : internet, game online, social behaviour